1997
DOI: 10.1097/00006842-199711000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in Fibromyalgia Compared With Rheumatoid Arthritis

Abstract: Fibromyalgia seems to be associated with increased risk of victimization, particularly adult physical abuse. Sexual, physical, and emotional trauma may be important factors in the development and maintenance of this disorder and its associated disability in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
67
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(78 citation statements)
references
References 26 publications
8
67
0
3
Order By: Relevance
“…CFS/FM patients’ preoccupations may, notably, reflect deep disappointment and frustration about their failed strivings for physical or mental achievement, as well as approval from others. Such strivings – which have been described as a central theme in the illness narratives of CFS/FM patients [37]– may be psychodynamically linked to personality factors, such as a vulnerable self-esteem [38, 39, 40], narcissistic or perfectionistic tendencies [41, 42]and, not uncommonly, early victimisation experiences [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFS/FM patients’ preoccupations may, notably, reflect deep disappointment and frustration about their failed strivings for physical or mental achievement, as well as approval from others. Such strivings – which have been described as a central theme in the illness narratives of CFS/FM patients [37]– may be psychodynamically linked to personality factors, such as a vulnerable self-esteem [38, 39, 40], narcissistic or perfectionistic tendencies [41, 42]and, not uncommonly, early victimisation experiences [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is, on the one hand, based on the fact that negative life events (often combined with a viral infection or a physical trauma) [10, 11, 12, 13], victimisation experiences [14, 15]and the mental or physical stress of an overactive lifestyle [16, 17]have been found to be frequently associated with the development of CFS/FM. On the other hand, there is ample evidence that CFS and FM patients are confronted with severe psychosocial stress related to coping and adaptation problems, a lack of comprehension by the environment and uncertainties surrounding the nature and prognosis of their condition [18, 19, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the sample was comprised of individuals with FM, a pain condition associated with a high prevalence of childhood maltreatment and comorbid depression and anxiety (7, 27). Thus, the findings may not generalize to healthy individuals or to those with other chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…FM is a condition characterized by widespread musculoskeletal pain of unknown etiology (21). Of relevance for the current study, the prevalence of depression and anxiety symptoms are elevated among patients with FM even relative to those with other chronic pain conditions (7, 22). In fact, some investigators have suggested that FM be considered an affective spectrum disorder (23).…”
mentioning
confidence: 92%
“…In particular, victims of child abuse are at greater risk of developing stress-related immune disorders, including allergies, asthma, and autoimmune diseases (Dube et al 2009), as well as metabolic and vascular diseases, including Type 2 diabetes, hypertension, and heart disease (Dong et al 2004; Fuller-Thomson et al 2009; Lee et al 2014c; Rich-Edwards et al 2010; Riley et al 2010). Adult survivors of childhood abuse are over-represented in many clinical patient groups, including irritable bowel syndrome, fibromyalgia, and extreme obesity (Drossman et al 1990; Walker et al 1997). Diverse health risks likely arise from the cumulative impact of biological dysregulation beginning during early development and continuing into adulthood (Danese and McEwen 2012).…”
Section: Introductionmentioning
confidence: 99%